FAKTOR-FAKTOR PENENTU KUALITAS HUBUNGAN DAN KEDEKATAN HUBUNGAN DALAM PEMBERIAN LAYANAN KREDIT PERBANKAN KEPADA USAHA MIKRO SERTA PENGARUHNYA TERHADAP KEPUASAN DAN LOYALITAS NASABAH - Komar Hariyanto (Journal of Business & Banking, 2014)
Customer loyalty has a very powerful effect on keeping the business sustainability. In addition,loyalty is affected by customer satisfaction which, in turn, is affected by the quality of the relationshipbetween customers and the business. Service improvement is done by maintaining relationshipquality and intimacy. This study examines the impact of interaction between bankingservices and its relationship with quality (which is conceptualized on customer interaction withinterpersonal services and customer interaction with the environment) and intimacy (which isconceptualized by employees hospitality and employees credibility). This study proposes amodel of conceptual relation between quality and intimacy and its impact on satisfaction andloyalty for micro enterprises in Surabaya and its entire (Sidoarjo, Gresik, Mojokerto). Datawere taken from 123 samples and analyzed using Structural Equation Modeling (SEM). Itshows that customer interaction with environment has greater effect the quality, and employeescredibility has also greater effect on intimacy. The quality has no significant affect onsatisfaction, but intimacy significantly affects satisfaction, and customer satisfaction also significantlyaffects loyalty.